Evolving therapies in chronic obstructive pulmonary disease. (May 2014) - D'Urzo, Anthony D; Maleki-Yazdi, M Reza; McIvor, R Andrew
The global prevalence of chronic obstructive pulmonary disease (COPD) is rising, although the disease is often underdiagnosed or misdiagnosed as asthma. Early diagnosis and intervention in the primary care setting may improve outcomes and reduce the overall burden of COPD and its comorbidities. Bronchodilators are the mainstay of pharmacologic treatment in international and national guidelines, with long-acting agents administered alone or as part of a combination regimen in patients who are persistently symptomatic and/or at high risk of COPD exacerbations. Here, we report results of a systematic literature search to review the evidence supporting several approved bronchodilator monotherapies, as well as dual bronchodilator treatment, combination therapy with inhaled corticosteroids plus one or two bronchodilators and other emerging COPD treatment options.